Method for treating lithium-containing oilfield produced water
Patent Information
- Application Number
- CN202311526791.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-15
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-11-15
AI Technical Summary
[0005]本发明的目的是为了克服现有技术存在的不适合提取锂浓度明显更低的低品位油田采出水中的锂的问题,提供一种处理含锂油田采出水的方法,采用该方法能够以较高的纯度和收率从上述低品位的含锂油田采出水中提取锂,并且工艺简单,生产成本低,提锂周期短
[0007]采用本发明提供的方法,能够以较高的纯度和收率从上述锂浓度低的含锂油田采出水中提取锂,并且工艺简单,生产成本低,特别适合于处理这种低品位的含锂油田采出水。相对于传统的晒盐等方式,本发明的方法还不受天气和场地的影响,并且提锂周期短,具有显著的经济效益。
Smart Images

Figure CN120004434B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of water treatment, and more specifically to a method for treating produced water from lithium-containing oil fields. Background Technology
[0002] Lithium is the lightest metal in nature and is widely used in energy, electronics, medical, nuclear industry, aerospace and other fields.
[0003] Global lithium resources are mainly distributed in South America, Australia, and China. Chile is the world's largest lithium producer. my country also possesses relatively abundant lithium resources, with Qinghai and Tibet having the largest reserves. With the rapid rise in lithium prices, my country's lithium mining capacity will continue to expand in the future. Currently, commonly used methods for lithium extraction from brine include adsorption, precipitation, extraction, and membrane separation. Each method has its advantages and disadvantages. For example, extraction is highly efficient, but the extractant is expensive, highly corrosive, and pollutes the environment; precipitation is simple to operate but only suitable for brines with low magnesium-to-lithium ratios; adsorption is low-cost and simple to operate, but the adsorption capacity of the adsorbent is relatively low; membrane separation technology is simple to operate and environmentally friendly, but the membranes used are heavily reliant on imports, resulting in high costs.
[0004] CN1511964A discloses a method for extracting lithium from salt lake brine—the adsorption method. This method has a simple process flow and is environmentally friendly, but it is only suitable for lithium-containing old brine from Qinghai salt lakes and concentrated lithium-containing brine from salt fields. The resulting lithium-rich solution is used to prepare lithium carbonate and lithium chloride. CN109987618A discloses a method for preparing battery-grade lithium carbonate, using a membrane separation system to separate magnesium and lithium from diluted salt lake brine. However, the multi-stage concentration in this method increases the energy consumption of the concentration process and reduces the concentration efficiency. The magnesium-to-lithium ratio in the lithium-rich solution after nanofiltration is still relatively high, resulting in a high magnesium-to-lithium ratio in the subsequent concentrate, increasing the pressure on deep magnesium removal and precipitation conversion processes, and increasing the cost of obtaining lithium carbonate products. The above methods are mainly for lithium resource extraction from high-grade salt lake brines, and lithium extraction is simple, but they are not suitable for lithium extraction from low-grade oilfield produced water with significantly lower lithium concentrations. Summary of the Invention
[0005] The purpose of this invention is to overcome the problem that existing technologies are unsuitable for extracting lithium from low-grade oilfield produced water with significantly lower lithium concentrations, and to provide a method for treating lithium-containing oilfield produced water. This method can extract lithium from the aforementioned low-grade lithium-containing oilfield produced water with high purity and yield, and the process is simple, with low production costs and a short lithium extraction cycle.
[0006] To achieve the above objectives, the present invention provides a method for treating produced water from lithium-containing oilfields, the method comprising: (1) Ultrafiltration of produced water from lithium-containing oilfields; (2) Using lithium adsorption material, Li adsorption is performed on ultrafiltration produced water containing lithium from the oilfield to obtain produced water with Li adsorption; the lithium adsorption material is desorbed to obtain desorbed liquid; (3) The desorption solution is enriched with monovalent ions to obtain a monovalent ion-poor solution and a monovalent ion-enriched solution; (4) The monovalent ion enrichment solution is subjected to forward osmosis to obtain forward osmosis concentrate; (5) The forward osmosis concentrate is subjected to bipolar membrane electrodialysis to obtain an alkaline solution containing LiOH.
[0007] The method provided by this invention can extract lithium from produced water from lithium-containing oilfields with low lithium concentrations, achieving high purity and yield. Furthermore, the process is simple, with low production costs, making it particularly suitable for treating such low-grade lithium-containing oilfield produced water. Compared to traditional methods such as salt production, the method of this invention is unaffected by weather and site conditions, and has a short lithium extraction cycle, resulting in significant economic benefits. Attached Figure Description
[0008] Figure 1 The product of Preparation Example 1, the steps of Preparation Example 1 (1) Modified Li 1.33 Mn 1.67 O4, and the infrared spectrum of polyvinyl alcohol used in Preparation Example 1; Figure 2 The product of Preparation Example 1 and the modified Li 1.33 Mn 1.67 XRD pattern of O4; Figure 3 This is a SEM (scanning electron microscope) image of the product prepared in Example 1; Figure 4 This is a photograph of the product from Preparation Example 1. Detailed Implementation
[0009] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0010] This invention provides a method for treating produced water from lithium-containing oilfields, the method comprising: (1) Ultrafiltration of produced water from lithium-containing oilfields; (2) Using lithium adsorption material, Li adsorption is performed on ultrafiltration produced water containing lithium from the oilfield to obtain produced water with Li adsorption; the lithium adsorption material is desorbed to obtain desorbed liquid; (3) The desorption solution is enriched with monovalent ions to obtain a monovalent ion-poor solution and a monovalent ion-enriched solution; (4) The monovalent ion enrichment solution is subjected to forward osmosis to obtain forward osmosis concentrate; (5) The forward osmosis concentrate is subjected to bipolar membrane electrodialysis to obtain an alkaline solution containing LiOH.
[0011] The inventors of this invention have discovered that when the above method is used, lithium can be fully extracted from produced water in lithium-containing oilfields. The above method can achieve high purity and extraction rate, and the process is simple, easy to operate, and consumes little energy. It is particularly suitable for treating low-grade lithium-containing oilfield produced water with low lithium concentration.
[0012] According to the present invention, preferably, in step (1), the ultrafiltration operating conditions include: a temperature of 5-30°C and a pressure of 0.1-0.4 MPa. This ensures more thorough removal of impurities such as suspended solids, colloids, and macromolecular organic matter from lithium-containing oilfield produced water.
[0013] According to a preferred embodiment of the present invention, the ultrafiltration membrane used has a molecular weight cutoff of 10,000-30,000 Da. For example, the VFU-030 tubular ultrafiltration membrane from Jia Rong Technology Co., Ltd. can be used.
[0014] It is understandable that ultrafiltration produces ultrafiltration retentate and ultrafiltration permeate. Suspended solids and other impurities in lithium-containing oilfield produced water are retained in the ultrafiltration retentate, while lithium, which is of particular interest, enters the ultrafiltration permeate. "Ultrafiltration produced water from lithium-containing oilfields" refers to the ultrafiltration permeate.
[0015] According to the present invention, preferably, in step (2), the operating conditions for Li adsorption include: an adsorption flow rate of 1.8-3 BV / h, a temperature of 8-30℃, and a time of 5.5-8h.
[0016] Here, BV represents the filling volume of the lithium adsorbent material. In adsorption operations, the adsorbent material is typically filled into a container (such as an adsorption column), and then the fluid to be adsorbed is continuously passed through the adsorption column to contact the adsorbent material for adsorption. 1.8-3 BV / h means that the volume of fluid per hour is 1.8-3 times the filling volume of the lithium adsorbent material.
[0017] After adsorption is complete, most of the lithium in the produced water from lithium-containing oilfields is adsorbed onto the lithium adsorbent material. The liquid phase (which can be called lithium-poor ultrafiltrate at this time) contains less lithium, and the lithium-poor ultrafiltrate can be treated centrally as waste liquid.
[0018] According to the present invention, preferably, in step (2), the desorption operating conditions include: a desorption flow rate of 1.8-3 BV / h for the desorbent, a temperature of 8-30°C, and a time of 5.5-8 h. The desorbent is continuously passed through a container filled with lithium adsorbent material that has completed adsorption. The lithium adsorbed on the lithium adsorbent material enters the desorption solution through the above desorption process.
[0019] Preferably, the desorbent is selected from water or an inorganic acid solution. The concentration of the inorganic acid in the inorganic acid solution can be 0.1-1 mol / L. The inorganic acid can be hydrochloric acid.
[0020] According to a particularly preferred embodiment of the present invention, Li in the desorption solution + Concentration of 420-630 mg / L, Na + Concentration of 150-170 mg / L, K + Concentration of 35-40 mg / L, Mg 2+ Concentration of 74-80 mg / L, Ca 2+ The concentration is 4-6 mg / L.
[0021] According to the present invention, preferably, the method of enriching monovalent ions is selected from selective electrodialysis and / or nanofiltration, more preferably selective electrodialysis. It is understood that, in order to achieve monovalent ion enrichment, selective electrodialysis refers to electrodialysis capable of selectively enriching monovalent ions. The system used in selective electrodialysis has the following structure: between the anode chamber and the cathode chamber, there are sequentially arranged monovalent ion selective cation membranes, concentrate chambers, monovalent ion selective anion membranes, desalinated water chambers, monovalent ion selective cation membranes, concentrate chambers, and monovalent ion selective anion membranes, with the two plates connected to a DC power supply. In selective electrodialysis, selective permeation of anions and cations is achieved through selective anion and cation membranes. Membranes with monovalent ion selective permeability can be selected to achieve the above-mentioned monovalent ion enrichment, such as the monovalent ion selective anion membrane APX-D and the monovalent ion selective cation membrane CXP-S purchased from ASTOM Corporation, Japan.
[0022] It is understandable that the functions achievable in electrodialysis are highly dependent on the selection of the membrane. Therefore, specific electrodialysis objectives can be achieved by selecting membranes with specific functions.
[0023] According to the present invention, preferably, the operating conditions for the selective electrodialysis include: a current density of 400-500 A / m 2 Temperature 10-30℃, time 4-6 hours.
[0024] In operation, the desorption solution can be sent into the desalination chamber of the selective electrodialysis system, and pure water can be used as the starting solution for the concentrate. Under the action of the electric field, monovalent ions pass through the membrane from the desalination chamber into the concentrate chamber, while most divalent ions are retained. This results in a low lithium ion content in the desalination chamber, ultimately yielding a monovalent ion-poor solution; the concentrate chamber has a high lithium ion content, ultimately yielding a monovalent ion-rich solution.
[0025] According to a particularly preferred embodiment of the present invention, when the lithium ion concentration in the lean monovalent ionic liquid is higher than 0.5 times the lithium ion concentration in the ultrafiltered lithium-containing oilfield produced water, and the magnesium-to-lithium mass ratio in the lean monovalent ionic liquid does not exceed 50, the method further includes: mixing the lean monovalent ionic liquid and the ultrafiltered lithium-containing oilfield produced water for joint Li adsorption in step (2). This ensures sufficient lithium recovery. When the above conditions are not met, the lean monovalent ionic liquid and the lithium-deficient ultrafiltration liquid can be treated together as waste liquid for centralized treatment.
[0026] According to a particularly preferred embodiment of the present invention, in the monovalent ion enrichment solution: TDS (total dissolved solids) ≥ 10000 mg / L, preferably 10000-13000 mg / L; Li + Concentration of 880-1350 mg / L, Na + Concentration of 340-360 mg / L, K + Concentration of 70-85 mg / L, Mg 2+ The concentration is 6-8 mg / L.
[0027] According to the present invention, preferably, the operating conditions for the forward osmosis include: a temperature of 10-30°C and a time of 3-12 hours. Under these operating conditions, the volume of the forward osmosis concentrate is generally 0.3-0.5 times that of the monovalent ion enrichment solution.
[0028] It is understood that forward osmosis utilizes the osmotic pressure difference between the solutions on both sides of the membrane as the driving force. The two sides of the membrane are the solution to be treated and the draw solution, respectively (in the scheme of this invention, ultrafiltration-processed water from lithium-containing oil fields or the mother liquor obtained from the subsequent extraction of LiOH from LiOH-containing alkaline solutions can be used as the draw solution). Driven by the osmotic pressure difference, water molecules in the solution to be treated pass through the membrane into the draw solution, continuously concentrating the solution to obtain forward osmosis concentrate. Due to the continuous influx of water molecules, the draw solution becomes increasingly diluted, resulting in a diluted forward osmosis draw solution. Using the preferred forward osmosis operating conditions provided by this invention further ensures the concentration effect.
[0029] The membrane used for forward osmosis can be the HTITAES forward osmosis membrane from Shanghai Tongqin Environmental Protection Technology Co., Ltd.
[0030] According to a particularly preferred embodiment of the present invention, when the lithium ion concentration in the forward osmosis dilute extract is higher than 0.5 times the lithium ion concentration in the ultrafiltration produced water from lithium-containing oilfields, and the magnesium-to-lithium mass ratio of the forward osmosis dilute extract does not exceed 40, the method further includes: mixing the forward osmosis dilute extract and the ultrafiltration produced water from lithium-containing oilfields for joint Li adsorption in step (2). When the above conditions are not met, the forward osmosis dilute extract and the lithium-poor ultrafiltration solution can be treated together as waste liquid for centralized treatment.
[0031] According to a particularly preferred embodiment of the present invention, in the forward permeation concentrate: Li + Concentration of 2000-4200 mg / L, Na + Concentration of 670-830 mg / L, K + Concentration of 170-180 mg / L, Mg 2+ The concentration is 13-16 mg / L.
[0032] The bipolar membrane electrodialysis system has the following structure: between the anode and cathode chambers, there is a bipolar membrane, an acid chamber, a monovalent ion-selective anion membrane (e.g., an APX-D membrane purchased from ASTOM Corporation, Japan), a desalination chamber, a monovalent ion-selective cation membrane (e.g., a CXP-S membrane purchased from ASTOM Corporation, Japan), an alkali chamber, and the bipolar membrane again. In other words, the bipolar membrane electrodialysis system is a three-chamber system with the above structure. Ruthenium-coated titanium cathode and anode plates can be connected to the two sides respectively, and the two plates are connected to a DC power supply. The bipolar membrane can be a BPX bipolar membrane purchased from Hangzhou Kerui Environmental Energy Technology Co., Ltd.
[0033] According to the present invention, preferably, the operation mode of the bipolar membrane electrodialysis includes: using forward osmosis concentrate as feed water to the desalination chamber, operating voltage of 2-3V, and current density of 600-900A / m³. 2 The time is 4-5 hours. Pure water can be used as the feed water for both the acid and alkali chambers.
[0034] Under the influence of an electric field, Li is permeating the concentrated water. + It passes through the monovalent ion-selective cation membrane to reach the alkaline chamber, where it reacts with the OH- generated by the bipolar membrane. - This forms an alkaline solution containing LiOH (which may also contain a small amount of KOH); Cl - It passes through the monovalent ion-selective anion membrane to reach the acid chamber, where it reacts with H+ generated by the bipolar membrane. + An HCl acid solution is formed. This HCl solution can be used as a desorbent for lithium adsorbent materials or as a washing solution for cleaning forward osmosis systems. This reduces production costs, maximizes resource utilization, and avoids environmental impact. The desalinated brine discharged from the desalination chamber can also be mixed with a monovalent ion enrichment solution for further forward osmosis.
[0035] The lithium ion concentration in the LiOH-containing alkaline solution obtained from the alkali chamber can be 0.8-1.6 mol / L.
[0036] According to the present invention, preferably, after step (5), the method further includes: extracting LiOH from the alkaline solution containing LiOH, and contacting LiOH with carbon dioxide to react and obtain lithium carbonate.
[0037] The specific method for extracting LiOH from the LiOH-containing alkaline solution is not particularly limited, but preferably, the method is evaporation and concentration at a temperature of 80-100℃. After evaporation and concentration, a mixture of lithium hydroxide and the mother liquor is obtained. This mixture is then subjected to solid-liquid separation (e.g., centrifugation, filtration) to obtain lithium hydroxide and the mother liquor separately. The mother liquor can be used as the draw solution for forward osmosis. Extracting LiOH through evaporation and concentration can improve the purity of the prepared lithium carbonate.
[0038] The specific method for contacting LiOH and carbon dioxide can include: dissolving LiOH in water to obtain a LiOH concentration of 85-100 g / L; contacting this solution with carbon dioxide gas in a gas-liquid reactor at 23-27°C, and reacting until the liquid phase pH reaches 11-12.5. After the reaction, a precipitate is obtained. The precipitate is washed, filtered, and dried (at a temperature of 30-90°C for 2-24 hours) to obtain lithium carbonate. Using the method provided by this invention, lithium carbonate with high purity is obtained.
[0039] According to the present invention, preferably, the produced water quality of lithium-containing oilfields includes: Li + The concentration is 25-80 mg / L, and the concentration of alkaline earth metal ions is 1000-1500 mg / L. Alkaline earth metal ions generally include calcium ions and magnesium ions.
[0040] More preferably, the quality of produced water from lithium-containing oilfields includes: Li + Concentration of 35-70 mg / L, Na + Concentration of 3100-3500 mg / L, K + Concentration of 290-320 mg / L, Mg 2+ Concentration of 1100-1350 mg / L, Ca 2+ Concentration of 35-55 mg / L, Cl - Concentration of 8700-9000 mg / L, SO4 2- The concentration is 1700-2100 mg / L, the pH is 7.5-8.5, the total organic matter is 500-1600 mg / L, and the total dissolved solids are 35000-38000 mg / L.
[0041] The method provided by this invention is particularly suitable for lithium-containing oilfield produced water, such as that which is difficult to extract lithium from under normal circumstances, and can extract lithium therefrom with high purity and extraction rate.
[0042] The method provided by this invention is not limited by weather or salt production sites, and shortens the lithium extraction cycle. The concentration of the lithium-containing solution through forward osmosis significantly reduces costs; the application of bipolar membrane electrodialysis and a gas-liquid reactor allows for the direct acquisition of lithium carbonate products with good continuity and high purity. Furthermore, the process is simple, easy to operate, consumes little energy, and yields higher lithium purity than traditional processes, resulting in significant economic benefits.
[0043] According to a particularly preferred embodiment of the present invention, the lithium adsorbent material includes a framework and a lithium ion sieve material dispersed in the framework, the lithium ion sieve material being connected to the framework by a coupling agent, the framework being provided by a cross-linked or uncross-linked polyhydroxy polymer.
[0044] The lithium adsorbent material preferably provided by this invention has good hydrophilicity, stable structure, acid and alkali resistance, and high lithium adsorption capacity, making it more suitable for practical applications.
[0045] According to the present invention, preferably, the average particle size of the lithium adsorbent material is 1-5 mm, more preferably 2-4 mm.
[0046] Preferably, the mass content of the lithium ion sieve material is 10-80 wt% relative to the mass of the lithium adsorbent material, more preferably 68-77 wt% (for example, it can be 68 wt%, 69 wt%, 70 wt%, 71 wt%, 72 wt%, 73 wt%, 74 wt%, 75 wt%, 76 wt%, 77 wt%, and any two of the above values within the range).
[0047] Preferably, the specific surface area of the lithium adsorbent material is 10-500 m². 2 / g, more preferably 10-45 m 2 / g (for example, 10m) 2 / g, 15m 2 / g、20m 2 / g、25m 2 / g、30m 2 / g、35m 2 / g、40m 2 / g、45m 2 / g and the range formed by any two of the above values, and the values within that range).
[0048] Preferably, the average pore size of the lithium adsorbent material is 0.1-10 μm, more preferably 2-5 μm (for example, it can be 2 μm, 3 μm, 4 μm, 5 μm, or any two of the above values within a range).
[0049] Preferably, the pore volume of the lithium adsorbent material is 10-100 cm³. 3 / g, more preferably 50-85cm 3 / g (for example, 50cm 3 / g、55cm 3 / g、60cm 3 / g、65cm 3 / g, 70cm 3 / g, 75cm 3 / g、80cm 3 / g、85cm 3 / g and the range formed by any two of the above values, and the values within that range).
[0050] Preferably, at 25°C, the lithium adsorbent material has a water absorption rate of 0.1-0.18 g / g for pure water and a volume swelling rate of 2-10% (for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or any two of the above values within a range).
[0051] According to the present invention, preferably, the lithium-ion sieve material is selected from titanium-based and / or manganese-based lithium-ion sieve materials.
[0052] Preferably, the average particle size of the lithium-ion sieve material is 10-500 μm (for example, it can be 10 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, or any two of the above values within a range).
[0053] Preferably, the polyhydroxy polymer is selected from at least one of polyvinyl alcohol, chitosan, polyethylene glycol and carboxymethyl cellulose, and more preferably polyvinyl alcohol.
[0054] Preferably, the coupling agent is selected from silane coupling agents.
[0055] Preferably, the silane coupling agent is selected from at least one of mercapto-containing silane coupling agents and epoxy-containing silane coupling agents, and is more preferably an epoxy-containing silane coupling agent.
[0056] More preferably, the epoxy-containing silane coupling agent is selected from at least one of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-(2,3-epoxypropoxypropyl)methyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
[0057] According to the present invention, preferably, the lithium-ion sieve material is a lithium-ion sieve material modified with polyphenols.
[0058] Preferably, the method for polyphenol modification includes: mixing lithium ion sieve material and polyphenol to modify the lithium ion sieve material.
[0059] Preferably, the mixing is carried out in a solution environment.
[0060] Preferably, the mass ratio of lithium ion sieve material to polyphenol is 1:(0.08-0.3).
[0061] Preferably, the mixing time is 1-3 hours.
[0062] The polyphenols are selected from at least one of tannic acid, tea polyphenols, dopamine, sennaol, epicatechin, luteolin, calciferol, myricetin and genistein, preferably at least one of tannic acid, tea polyphenols and dopamine.
[0063] The present invention also provides a method for preparing lithium adsorbent materials, the method comprising: In the presence of a coupling agent, a polyhydroxy polymer and a lithium-ion sieve material are coupled together.
[0064] It is understood that lithium-ion sieve materials refer to materials with lithium adsorption capabilities. When applied for adsorption, hydrogen ions and lithium ions in the lithium-ion sieve material exchange, thereby enriching the lithium ions onto the lithium adsorbent material. When preparing lithium adsorbent materials using lithium-ion sieve materials, the lithium-ion sieve material can be a lithium-ion sieve rich in hydrogen ions; or it can be a lithium-ion sieve precursor with a lower hydrogen ion content but a higher lithium ion content. Before application for adsorption, it is acid-washed to replace the lithium ions with hydrogen ions, thus obtaining the lithium-ion sieve. That is, the lithium-ion sieve material described in this application includes both lithium-ion sieves and lithium-ion sieve precursors.
[0065] The inventors of this invention discovered in their research that the lithium adsorbent material prepared using the above method exhibits a large saturated adsorption capacity for lithium, a high extraction rate, and high selectivity. Specifically, the polyhydroxy polymer is hydrophilic, possesses a network structure in its framework, and has high porosity and specific surface area, resulting in a high lithium loading capacity, which is beneficial for improving the lithium adsorption rate and amount. After coupling, the compatibility between the polyhydroxy polymer and the lithium-ion sieve material is also better; the lithium-ion sieve material is less prone to agglomeration and is more uniformly distributed on the polyhydroxy polymer, further enhancing its adsorption effect.
[0066] The specific type of coupling agent is not particularly limited, as long as it can simultaneously connect the polyhydroxy polymer and the lithium-ion sieve material. However, preferably, the coupling agent is selected from silane coupling agents. Silane coupling agents generally have a YR-Si-X3 structure, where Y is an organic functional group, R is an alkylene group, and X is an alkoxy group. The alkoxy group can be hydrolyzed to obtain a hydroxyl group, thereby reacting with inorganic substances such as lithium-ion sieve materials; the organic functional group can react with organic substances such as polyvinyl alcohol.
[0067] According to the present invention, preferably, the silane coupling agent is selected from at least one of thiol-containing silane coupling agents and epoxy-containing silane coupling agents, and more preferably an epoxy-containing silane coupling agent. It is understood that thiol and epoxy groups refer to the groups contained in the YR structure of the silane coupling agent.
[0068] According to the present invention, more preferably, the epoxy-containing silane coupling agent is selected from at least one of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-(2,3-epoxypropoxypropyl)methyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. Thiol-containing silane coupling agents include γ-mercaptopropyltriethoxysilane, etc.
[0069] According to the present invention, preferably, the polyhydroxy polymer is selected from at least one of polyvinyl alcohol, chitosan, polyethylene glycol, and carboxymethyl cellulose, more preferably polyvinyl alcohol. The weight-average molecular weight of the polyhydroxy polymer is not particularly limited, for example, it can be 50,000-250,000 g / mol. The degree of alcoholysis of polyvinyl alcohol can be 83-99%.
[0070] According to the present invention, preferably, the lithium-ion sieve material is selected from titanium-based and / or manganese-based lithium-ion sieve materials. For example, it can be LiMn2O4, Li... 1.6 Mn 1.6 O4, Li 1.33 Mn 1.67 O4, Li4Mn5O 12 , LiMnO, LiMnO2, Li2TiO3, Li 1.33 Ti 1.66O4, Li4Ti5O 12 Such lithium-ion sieve precursors, or their corresponding acid-washed lithium-ion sieves.
[0071] According to another preferred embodiment of the present invention, the lithium-ion sieve material is selected from aluminum-based lithium-ion sieve materials. For example, LiCl·2Al(OH)3·nH2O can be used. When using aluminum-based lithium-ion sieve materials, desorption of such lithium adsorbent materials containing adsorbed lithium ions can be completed using only pure water, without the need for acid solutions, thus reducing costs.
[0072] According to the present invention, preferably, the average particle size of the lithium-ion sieve material is 10-500 μm (for example, it can be 10 μm, 50 μm, 100 μm, 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 500 μm, or any two of the above values within a range). During preparation, the lithium-ion sieve material in powder form within the above particle size range can be used.
[0073] The aforementioned lithium-ion sieve materials can be obtained by purchase or prepared by the manufacturer. The preparation method can be a conventional method in the field. Taking the high-temperature solid-phase synthesis preparation method of Li2TiO3 as an example: anatase TiO2 and Li2CO3 (both referred to as solids) can be weighed at a molar ratio of 1:1-1.2 and added to a stainless steel ball mill jar. Then, ethanol equivalent to 1.8-2.2 times the mass of the solids and stainless steel beads (with a diameter of 3-5 mm) equivalent to 18-25 times the mass of the solids can be added to the ball mill jar. The mixture is ball-milled at a speed of 180-220 rpm for 3.5-4.5 h using a planetary ball mill. After drying at 35-45℃, the mixture is placed in a muffle furnace and calcined in an air atmosphere at 750-850℃ for 5-7 h. After cooling, the mixture is eluted with 0.4-0.6 mol / L HCl solution for 18-28 h to obtain lithium-ion adsorbent powder Li2TiO3.
[0074] According to the present invention, preferably, prior to coupling, the method further includes: mixing the lithium-ion sieve material with polyphenols to modify the lithium-ion sieve material.
[0075] According to the present invention, preferably, the mixing is carried out in a solution environment. For example, it can be carried out in an aqueous solution environment of polyphenols.
[0076] Preferably, the mass ratio of lithium-ion sieve material to polyphenol is 1:(0.08-0.3). In the aqueous solution, the concentration of polyphenol can be 0.1-1 mg / L.
[0077] Preferably, the mixing time is 1-3 hours. During mixing, stirring can be performed (at a speed of 300-500 rpm), and the mixing can be carried out at room temperature.
[0078] Preferably, the polyphenol is selected from at least one of tannic acid, tea polyphenols, dopamine, sennaol, epicatechin, luteolin, calciferol, myricetin and genistein, and more preferably at least one of tannic acid, tea polyphenols and dopamine.
[0079] The above modifications generally enable the formation of a polyphenol modified layer of about 10-50 nm on the surface of the lithium ion screen material, resulting in a large number of hydroxyl groups on the surface of the lithium ion screen material. This leads to better compatibility with the polyhydroxy polymer skeleton and easier uniform dispersion in the skeleton, further ensuring that the lithium ion screen material will not accumulate or be lost during long-term scouring by water flow and pressure.
[0080] After mixing and stirring, the material can be separated into solid and liquid phases (e.g., by centrifugation), and the resulting solid material can be dried (at a temperature of 30-80℃ for 4-12 hours).
[0081] Using the above method, a 10-50 nm polyphenol modification layer can generally be formed on the surface of lithium-ion sieve materials. Understandably, the particle size of the lithium-ion sieve materials does not change significantly before and after modification.
[0082] According to the present invention, preferably, the mass ratio of the polyhydroxy polymer, the lithium-ion sieve material, and the coupling agent is 1:(0.1-5):(0.05-1.5), more preferably 1:(3-5):(0.1-1.5). This allows for a more uniform and efficient loading of the lithium-ion sieve powder material onto the polyvinyl alcohol framework.
[0083] According to the present invention, the preferred coupling conditions include: a temperature of 50-90°C (e.g., 50°C, 60°C, 70°C, 80°C, 90°C), a time of 1-24 hours (e.g., 1 hour, 3 hours, 5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours, 22 hours, 24 hours), and a pH of 1-3 (e.g., 1, 1.5, 2, 2.5, 3). The pH can be adjusted using hydrochloric acid.
[0084] When in use, polyhydroxy polymers are generally used in the form of aqueous solutions, and the concentration of polyhydroxy polymers in the aqueous solution can be 8-16 wt%.
[0085] Preferably, after coupling, the method further includes: aging and granulating the material sequentially.
[0086] Preferably, the aging conditions include a temperature of 50-70°C and a time of 0.2-2 hours.
[0087] Preferably, granulation is performed to achieve a material particle size of 1-5 mm, more preferably 2-4 mm. This can be carried out in a granulator. The particle size of the granulated material may not be completely uniform and can fall within a range.
[0088] According to the present invention, preferably, the method further includes: cross-linking the granulated product under the action of a cross-linking agent. It is understood that the cross-linking agent causes the backbone of the lithium adsorbent material, i.e., the polyhydroxy polymer, to cross-link.
[0089] According to the present invention, preferably, the crosslinking method is as follows: the granulated product is immersed in a crosslinking agent solution with a crosslinking agent concentration of 0.1-1 wt% (e.g., 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, or 1 wt%), the crosslinking temperature is 20-40°C (e.g., 20°C, 25°C, 30°C, 35°C, or 40°C), and the crosslinking time is 30-120 min (e.g., 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, or 120 min). Generally, the amount of crosslinking agent solution relative to 1 g of granulated product can be 80-150 ml.
[0090] After re-coupling, the above cross-linking process is carried out, resulting in a stronger bond between the polyhydroxy polymer and the lithium ion sieve material, a more stable structure, and a more acid and alkali resistant lithium adsorbent material.
[0091] According to the present invention, preferably, the crosslinking agent is selected from at least one aldehyde compound, and more preferably from at least one of C1-C5 monoaldehydes and C1-C5 dialdehydes. It is understood that the particle size of the material does not change significantly before and after crosslinking. The aldehyde group in the crosslinking agent can undergo an aldol condensation reaction with the hydroxyl group in the polyhydroxy polymer to form a crosslinked polyhydroxy polymer structure.
[0092] According to the present invention, preferably, the method further includes: acid washing of the crosslinked product after crosslinking. Before acid washing, the material can be dried (or oven-dried) at 50-70°C for 18-36 hours, and then circulated and acid-washed in an adsorption column using 0.05-0.3 mol / L hydrochloric acid for 0.5-2 hours. The acid-washed material can be circulated once more with deionized water for washing. Acid washing can replace lithium ions on the lithium-ion sieve material with hydrogen ions.
[0093] The present invention will be described in detail below through preparation examples.
[0094] In the following preparation example, the cross-linked material was dried, acid-washed, and washed with water as follows: the cross-linked material was dried in an oven at 60°C for 24 hours, then loaded into an adsorption column and circulated in the column with 0.1 mol / L HCl for 1 hour. The acid-washed material was then circulated once with deionized water and washed with water.
[0095] Preparation Example 1 (1) Take powder Li 1.33 Mn 1.67 O4 (average particle size of 300 μm) was mixed with an aqueous solution of tannic acid to make the mass ratio of lithium ion sieve material to polyphenol 1:0.1. The mixture was stirred at room temperature for 2 h (300 rpm), then centrifuged and the solid phase material was dried (at 60 °C for 8 h) to complete the modification of the lithium ion sieve material.
[0096] (2) Take a 15 wt% polyvinyl alcohol aqueous solution (degree of alcoholysis 88%, weight average molecular weight 89000 g / mol) and the modified Li prepared in step (1). 1.33 Mn 1.67 O4 powder was mixed and stirred evenly, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added to make polyvinyl alcohol: modified Li 1.33 Mn 1.67 The mass ratio of O4 to γ-(2,3-epoxypropoxy)propyltrimethoxysilane was 1:5:1.5, and the pH of the system was adjusted to 1 with 0.1 mol / L HCl. The mixture was stirred at 70 °C for 8 h and then aged in a 60 °C oven for 30 min to obtain a semi-solid product. This product was then extruded to obtain a material with a particle size of 2-3 mm.
[0097] (3) The material obtained in step (2) is immersed in a formaldehyde aqueous solution with a formaldehyde concentration of 0.1wt% at 20°C (the amount of crosslinking agent solution is 80ml relative to 1g of granulated product) for 120min to carry out crosslinking.
[0098] The cross-linked material is dried, acid-washed, and water-washed to obtain the product as follows: Figure 4 As shown.
[0099] Preparation Example 2 (1) Take powder Li 1.33 Mn 1.67 O4 (average particle size of 250 μm) was mixed with an aqueous solution of tannic acid to make the mass ratio of lithium ion sieve material to polyphenol 1:0.3. The mixture was stirred at room temperature for 1 h (400 rpm), then centrifuged and the solid phase material was dried (at 60 °C for 8 h) to complete the modification of the lithium ion sieve material.
[0100] (2) Take a 13wt% polyvinyl alcohol aqueous solution (degree of alcoholysis 88%, weight average molecular weight 89000 g / mol) and the modified Li prepared in step (1). 1.33 Mn 1.67O4 powder was mixed and stirred evenly, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added to make polyvinyl alcohol: modified Li 1.33 Mn 1.67 The mass ratio of O4 to γ-(2,3-epoxypropoxy)propyltrimethoxysilane was 1:3:0.8, and the pH of the system was adjusted to 2 with 0.1 mol / L HCl. The mixture was stirred at 50 °C for 24 h and then aged in an oven at 55 °C for 60 min to obtain a semi-solid product. The product was then extruded to obtain a material with a particle size of 2-3 mm.
[0101] (3) The material obtained in step (2) is immersed in a formaldehyde aqueous solution with a formaldehyde concentration of 1wt% at 30°C (the amount of crosslinking agent solution is 100ml relative to 1g of granulated product) for 30min to carry out crosslinking.
[0102] Preparation Example 3 (1) Take powder Li 1.33 Mn 1.67 O4 (average particle size of 350 μm) was mixed with an aqueous solution of tannic acid to make the mass ratio of lithium ion sieve material to polyphenol 1:0.08. The mixture was stirred at room temperature for 3 h (500 rpm), then centrifuged and the solid phase material was dried (at 60 °C for 8 h) to complete the modification of the lithium ion sieve material.
[0103] (2) Take a 10 wt% polyvinyl alcohol aqueous solution (degree of alcoholysis 88%, weight average molecular weight 89000 g / mol) and the modified Li prepared in step (1). 1.33 Mn 1.67 O4 powder was mixed and stirred evenly, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added to make polyvinyl alcohol: modified Li 1.33 Mn 1.67 The mass ratio of O4 to γ-(2,3-epoxypropoxy)propyltrimethoxysilane was 1:3.5:0.1, and the pH of the system was adjusted to 3 with 0.1 mol / L HCl. The mixture was stirred at 90 °C for 1 h and then aged in a 70 °C oven for 120 min to obtain a semi-solid product. The product was then extruded to obtain a material with a particle size of 2-3 mm.
[0104] (3) The material obtained in step (2) is immersed in a formaldehyde aqueous solution with a formaldehyde concentration of 0.8wt% at 38°C for 80 minutes to carry out cross-linking.
[0105] Preparation Example 4 The preparation method is the same as in Example 1, except that in step (1), tannic acid is replaced with tea polyphenols.
[0106] Preparation Example 5 The preparation method of Example 1 was followed, except that in step (1), tannic acid was replaced with dopamine.
[0107] Preparation Example 6 The preparation method was carried out in accordance with Example 1, except that the coupling agent was replaced with γ-mercaptopropyltriethoxysilane.
[0108] Preparation Example 7 The preparation method of Example 1 was followed, except that in step (2), the coupling agent was replaced with 3-aminopropyltrimethoxysilane.
[0109] Preparation Example 8 The lithium adsorbent material was prepared according to the method of Preparation Example 1, except that the modification in step (1) was not performed.
[0110] Preparation Example 9 The lithium adsorbent material was prepared according to the method of Preparation Example 1, except that in step (2), γ-(2,3-epoxypropoxy)propyltrimethoxysilane was replaced with glutaraldehyde, and step (3) was not performed.
[0111] Preparation Example 10 The lithium adsorbent material was prepared according to the method of Preparation Example 1, except that the powder modification in step (1) was not performed; and in step (2), γ-(2,3-epoxypropoxy)propyltrimethoxysilane was replaced with glutaraldehyde.
[0112] Preparation Example 11 The lithium adsorbent material was prepared according to the method of Preparation Example 1, except that in step (2), no coupling agent was used.
[0113] Preparation Example 12 The lithium adsorbent material was prepared according to the method of Preparation Example 1, except that polyvinyl alcohol was not added in step (2) (that is, the polyvinyl alcohol aqueous solution in Preparation Example 1 was replaced with the same weight of water).
[0114] Preparation Example 13 The lithium adsorbent material was prepared according to the method of Preparation Example 1, except that: Li 1.33 Mn 1.67 O4 was replaced with LiCl·2Al(OH)3·nH2O (average particle size is 300μm).
[0115] Test case The lithium adsorbent materials prepared in the above preparation examples were subjected to the following measurements: Adsorption capacity determination: Take 0.5g of lithium adsorbent material and 40ml of lithium-magnesium mixed solution (Li + Concentration of 100 ppm, Mg 2+ Static adsorption was performed using a mixed solution of lithium chloride and magnesium chloride (2000 ppm, pH 10.0, alkaline conditions). The change in adsorption capacity over time during the adsorption process was monitored, resulting in the kinetic curve (adsorption capacity - adsorption time). Adsorption kinetics reflects the rate of lithium adsorption by the adsorbent material.
[0116] After static adsorption for 24 hours, solid-liquid separation was performed, and the saturated adsorption capacity Q was calculated according to the following formula. Then, desorption was carried out with 0.5M HCl for 24 hours.
[0117]
[0118] Where Q is the saturated adsorption capacity in mg / g, reflecting the amount of adsorption at equilibrium; C0 and C are the initial and saturated ion concentrations in the solution, respectively, in mg / L; V is the volume of the adsorption solution in L; and M is the mass of the particulate lithium adsorbent in g. Ion concentrations were determined using ion chromatography (ICS-1100, DIONEX, America).
[0119] Lithium extraction efficiency is the ratio of the mass of lithium adsorbed by the lithium adsorbent material to the mass of lithium in the solution.
[0120] Selectivity coefficient This refers to the preference of lithium adsorbent materials for ions A and B when adsorbing ions A and B. A higher value indicates better selectivity for ions A, reflecting the selectivity of the lithium adsorbent material for different ions. The partition coefficient is the ratio of the two ions ( ). The ratio of ).
[0121]
[0122]
[0123] In the above formula, The concentration of each ion in the solution before adsorption is in mg / L; V represents the concentration of each ion at adsorption saturation, in mg / L; V is the solution volume, in mL. The mass of the lithium adsorbent material is expressed in grams (g).
[0124] The stability of the lithium adsorbent material for recycling was characterized using dynamic adsorption. The specific method was as follows: At 40℃, the lithium adsorbent material was packed into an adsorption column with a column volume of one fluidized bed (1 BV). Dynamic adsorption was performed, with 8 BV of brine injected and passed through the granules at a flow rate of 3 BV / h. After adsorption, desorption was performed using 2 BV of desorption solution, passed through the granules at a flow rate of 1-8 BV / h. The pH of the injected brine was 12, and the pH of the desorption solution was 3.
[0125] Table 1
[0126] The inventors of this invention also discovered that after adsorption and desorption were repeated 40 times using the products of Preparation Examples 1-6 and 13, the adsorption capacity of the products did not change significantly, and the mass loss ratio was less than 1%, indicating that the product prepared by the preferred scheme of this invention has a stable structure and good acid resistance. The mass loss ratio of Preparation Examples 9-10 was 2-5%. Furthermore, hardness tests using a Shore A hardness tester revealed that the products of Preparation Examples 1-6 had a Shore A hardness of 60-70, while the products of Preparation Examples 9-10 had a Shore A hardness less than 20. The particles of Preparation Examples 9-10 were brittle and easily broken in the dry state, the particles of Preparation Example 11 had a loose structure and were difficult to shape, and the particles of Preparation Example 12 disintegrated upon dissolving in water, making the above tests impossible. These results indicate that the granulated product has a stable structure and the powder is not easily detached after long-term use.
[0127] The inventors of this invention also discovered that the lithium adsorbent material in Preparation Examples 1-6 and Preparation Example 13 reaches adsorption equilibrium within 4 hours, and achieves 90% adsorption capacity within 30 minutes. The product provided by this invention has strong hydrophilicity, excellent water permeability, and can rapidly exchange water and ions.
[0128] Test Example 2 For the product of Preparation Example 1, and the modified Li in step (1) of Preparation Example 1 1.33 Mn 1.67 O4 and the polyvinyl alcohol used in Preparation Example 1 were characterized by infrared spectroscopy using a Fourier transform infrared spectrometer (FT-IR, MAGNA-IR 550). The results are shown in [Figure number missing]. Figure 1 .
[0129] Figure 1 It can be seen that the absorption peak of the tannic acid-modified lithium-ion sieve material is at 3400 cm⁻¹. -1 The hydroxyl peak appeared at 1637 cm⁻¹ -1 The appearance of the C=C peak indicates successful polyphenol modification. The IR peak at 3400 cm⁻¹ in polyvinyl alcohol (PVA) is also observed. -1 The large peak is the -OH peak, at 1733 cm⁻¹. -12927 cm -1 The peak is due to the stretching vibration of -C=C. The IR absorption peak of the product from Preparation Example 1 is at 2927 cm⁻¹. -1 3400cm -1 The peak (3400 cm⁻¹) of the tannic acid-modified lithium-ion sieve material was observed. -1 ) and the C=C characteristic peak of PVA (2927 cm⁻¹) -1 ), and 1197 cm -1 The nearby characteristic peaks are characteristic peaks of Si—O—C, indicating that the coupling agent in Preparation Example 1 successfully coupled PVA and polyphenol-modified lithium-ion sieve materials. Infrared characterization also revealed that in Preparation Examples 1-8, the coupling agent also successfully coupled PVA and polyphenol-modified lithium-ion sieve materials.
[0130] The product of Preparation Example 1 and the modified Li 1.33 Mn 1.67 The XRD pattern of O4 is shown below. Figure 2 It can be observed that the characteristic peaks and peak spacing of the product prepared in Example 1 are similar to those of Li. 1.33 Mn 1.67 The O4 powder was basically similar and showed no significant changes, indicating that the prepared product did not affect the composition of the lithium-ion sieve material. The corresponding situations in Preparation Examples 2-6 and Preparation Example 13 were similar to those in Preparation Example 1.
[0131] The products prepared in Preparation Examples 1-6 and Preparation Example 13 showed good powder dispersibility. Taking the product of Preparation Example 1 as an example, the results were obtained by scanning electron microscopy (SEM, S-4800) (see the results of Preparation Example 1 for details). Figure 3 Electron microscopy reveals an irregular porous structure within the particles, with pore sizes ranging from 2 to 5 μm. The lithium adsorbent powder is relatively uniformly dispersed and embedded within this microporous network framework. This structure prevents powder leakage during long-term use, thereby ensuring the product's strength and stability, and preventing significant performance changes after extended use. This demonstrates that polyphenol modification increases compatibility and improves the dispersibility of the lithium-ion sieve material on the product.
[0132] Test Example 3 The lithium adsorbent materials prepared in the above preparation examples were subjected to the following measurements: The specific surface area and pore volume were determined by measuring the adsorption-desorption isotherm of N2 on the lithium adsorbent material at 77 K and fitting the data to obtain the BET specific surface area and pore volume. The average aperture was determined by scanning electron microscopy. The water absorption rate A and volume swelling rate P were determined by placing a lithium adsorbent material with a mass of W0 and a volume of V0 in sufficient distilled water at 25℃. After 24 hours, the weight W1 and volume V1 were measured. A = (W1-W0) / W0, unit g / g; P = (V1-V0) / V0. The method for determining the mass content of lithium-ion sieve materials and framework relative to the mass of lithium adsorbent materials is as follows: For the products of Preparation Examples 1-8 and Preparation Example 13, the contents of Mn, Al, Si, C, and O elements were determined by X-ray photoelectron spectroscopy (XPS). The mass of the lithium-ion sieve was calculated based on the contents of Mn and Al, and the mass of the coupling agent was calculated based on the contents of Si. The remaining part was the mass of the framework. For the products of Preparation Examples 9-10, the content of Mn was determined by X-ray photoelectron spectroscopy (XPS). The mass of the lithium-ion sieve was calculated based on the content of Mn, and the remaining part was the mass of the framework.
[0133] The results are shown in Table 2-3.
[0134] Table 2
[0135] Table 3
[0136] In the preparation examples 4-7, the mass content of the lithium-ion sieve material was 71-72.5 wt%, and the mass content of the skeleton was 14-15 wt%.
[0137] The present invention will be described in detail below through embodiments. The composition of produced water from lithium-containing oilfields used in the following embodiments is shown in Table 4.
[0138] In the following examples and comparative examples, the concentrations of various ions in water were determined by ion chromatography (using a low-exchange-capacity ion exchange resin as a stationary phase to separate ionic substances, and continuously detecting changes in the conductivity of the effluent using a conductivity detector); the total organic carbon was determined by differential measurement (infrared radiation of a certain wavelength can be selectively absorbed by carbon dioxide, and within a certain concentration range, the intensity of carbon dioxide absorption of infrared radiation is proportional to the concentration of carbon dioxide, thus allowing for the determination of total carbon and inorganic carbon. The difference between total carbon and inorganic carbon is the total organic carbon); and the total dissolved solids were determined by contact conductivity (indirectly reflecting the TDS value through conductivity). The purity of lithium carbonate is determined by potentiometric titration (using hydrochloric acid as the titrant, the ion concentration changes continuously, causing the electrode potential to change accordingly; near the titration endpoint, the ion concentration changes abruptly, causing a sudden jump in the electrode potential, and the amount of lithium carbonate is calculated based on the amount of hydrochloric acid consumed).
[0139] The lithium extraction rate is calculated as: lithium mass in lithium carbonate / (volume of produced water from oilfield × lithium ion concentration).
[0140] In the following embodiments, the selective electrodialysis system has the following structure: between the anode chamber and the cathode chamber are sequentially arranged a monovalent ion selective cation membrane, a concentrate chamber, a monovalent ion selective anion membrane, a distillate chamber, a monovalent ion selective cation membrane, a concentrate chamber, and a monovalent ion selective anion membrane. The two electrodes are connected to a DC power supply. The monovalent ion selective anion membrane was purchased from ASTOM Corporation, Japan, model APX-D, and the monovalent ion selective cation membrane was purchased from ASTOM Corporation, Japan, model CXP-S.
[0141] The structure of the bipolar membrane electrodialysis system is as follows: Between the anode and cathode chambers are, in sequence, a bipolar membrane, an acid chamber, a monovalent ion-selective anion membrane (purchased from ASTOM Corporation, Japan, model APX-D), a desalination chamber, a monovalent ion-selective cation membrane (purchased from ASTOM Corporation, Japan, model CXP-S), an alkali chamber, and the bipolar membrane again. In other words, the bipolar membrane electrodialysis system is a three-chamber system with the above structure. Ruthenium-coated titanium cathode and anode plates are connected to the two sides respectively, and the two plates are connected to a DC power supply. The bipolar membrane was purchased from Hangzhou Kerui Environmental Energy Technology Co., Ltd., model BPX bipolar membrane. The feed water to the acid and alkali chambers is pure water.
[0142] Table 4
[0143] Example 1 (1) Ultrafiltration was performed on the produced water 1 from the lithium-containing oilfield. The ultrafiltration membrane (purchased from Jia Rong Technology Co., Ltd., model VFU-030 tubular ultrafiltration membrane) had a molecular weight cutoff of 30,000 Da, the ultrafiltration temperature was 15℃, and the pressure was 0.3 MPa.
[0144] (2) The ultrafiltration permeate (containing Li) + The lithium adsorbent material (concentration of 35 mg / L) and the lithium adsorbent material prepared in Preparation Example 13 were contacted in an adsorption column, and ultrafiltration permeate was pumped into the adsorption column at a rate of 3 BV / h, and adsorption was carried out at 30°C for 8 h.
[0145] After adsorption is complete, the lithium-poor ultrafiltrate is treated centrally as wastewater.
[0146] Lithium adsorbent material was desorbed using pure water as the desorbent at a flow rate of 3 BV / h at 25°C for 8 hours. The resulting eluent contained Li... + Concentration of 630 mg / L, Na + Concentration of 160 mg / L, K + Concentration of 40 mg / L, Mg 2+ Concentration of 80 mg / L, Ca 2+The concentration is 5 mg / L.
[0147] (3) The desorption solution was sent into the desalination chamber of the selective electrodialysis system, and pure water was sent into the concentrate chamber as the starting solution for the concentrate. The system was run for 6 hours at a temperature of 20°C and a current density of 600 A / m. 2 .
[0148] In selective electrodialysis, a monovalent ion-poor solution is obtained from the desalination chamber, and a monovalent ion-rich solution is obtained from the concentrate chamber.
[0149] In the monovalent ion enrichment solution, the TDS was 12600 mg / L, Li + Concentration of 1330 mg / L, Na + Concentration of 340 mg / L, K + Concentration of 85 mg / L, Mg 2+ The concentration is 8 mg / L.
[0150] The lithium ion concentration in the lean monovalent ionic liquid is 45 mg / L, and the magnesium-lithium mass ratio is 1.67. This satisfies the requirement that the lithium ion concentration in the lean monovalent ionic liquid is 0.5 times higher than the lithium ion concentration in the ultrafiltration lithium-containing oilfield produced water, and that the magnesium-lithium mass ratio in the lean monovalent ionic liquid does not exceed 50. The lean monovalent ionic liquid and the ultrafiltration lithium-containing oilfield produced water are mixed together to carry out Li adsorption in step (2).
[0151] (4) The monovalent ion enrichment solution was pumped into the forward osmosis unit (the membrane was purchased from Shanghai Tongqin Environmental Protection Technology Co., Ltd., model HTICATAES). The lithium-containing oilfield produced water after ultrafiltration was used as the draw solution for forward osmosis. The forward osmosis temperature was 25℃ and the time was 7 hours. Water molecules from the monovalent ion enrichment solution continuously permeated into the other side of the membrane. After forward osmosis, the monovalent ion enrichment solution yielded forward osmosis concentrate, the volume of which was 0.3 times that of the monovalent ion enrichment solution. The draw solution from forward osmosis was then used to obtain dilute draw solution from forward osmosis.
[0152] In the forward osmosis desalted extract, the lithium ion concentration is 56 mg / L and the magnesium-lithium mass ratio is 24, which satisfies the requirement that the lithium ion concentration in the forward osmosis desalted extract is 0.5 times higher than the lithium ion concentration in the ultrafiltration lithium-containing oilfield produced water, and that the magnesium-lithium mass ratio in the forward osmosis desalted extract does not exceed 40. The forward osmosis desalted extract and the ultrafiltration lithium-containing oilfield produced water are mixed together to carry out Li adsorption in step (2).
[0153] Li is permeating the concentrated water. + Concentration of 4120 mg / L, Na + Concentration of 670 mg / L, K + Concentration of 173 mg / L, Mg 2+ The concentration is 16 mg / L.
[0154] (5) In the bipolar membrane electrodialysis system, the forward osmosis concentrate is used as the feed water to the desalination chamber, the operating voltage is 3V, and the current density is 900A / m 2 Bipolar membrane electrodialysis was performed for 5 hours.
[0155] A dilute brine solution (with a lithium ion concentration of 0.41 g / L) is obtained from the desalination chamber and mixed with a monovalent ion enrichment solution for forward osmosis.
[0156] An acidic solution containing hydrogen chloride with a hydrogen ion concentration of 1.62 mol / L was obtained from the acid chamber and diluted for use as a desorbent for lithium adsorbent materials.
[0157] An alkaline solution containing LiOH was obtained from the alkali chamber, with a lithium ion concentration of 1.6 mol / L.
[0158] (6) Evaporate and crystallize the alkaline solution containing LiOH at 100°C to obtain a mixture of lithium hydroxide and mother liquor. After centrifuging and filtering the mixture, lithium hydroxide and mother liquor are obtained respectively.
[0159] The evaporated mother liquor is used as the draw solution for forward osmosis.
[0160] Lithium hydroxide was dissolved in water (resulting in a lithium hydroxide concentration of 99 g / L). The solution was then contacted with carbon dioxide gas in a gas-liquid reactor at 25°C until the liquid phase pH reached 12.1. The precipitate was washed, filtered, and dried to obtain lithium carbonate with a purity of 99.8% and a lithium extraction rate of 83%.
[0161] Example 2 (1) Ultrafiltration was performed on the produced water 2 from the lithium-containing oilfield. The ultrafiltration membrane (purchased from Jia Rong Technology Co., Ltd., model VFU-030 tubular ultrafiltration membrane) had a molecular weight cutoff of 30,000 Da, the ultrafiltration temperature was 16℃, and the pressure was 0.17 MPa.
[0162] (2) The ultrafiltration permeate (containing Li) + The lithium adsorbent material (concentration of 36.5 mg / L) and the lithium adsorbent material prepared in Preparation Example 13 were contacted in an adsorption column, and ultrafiltration permeate was pumped into the adsorption column at a rate of 2 BV / h, and adsorption was carried out at 10°C for 6 h.
[0163] After adsorption is complete, the lithium-poor ultrafiltrate is treated centrally as wastewater.
[0164] Lithium adsorbent material was desorbed using pure water as the desorbent at a flow rate of 2 BV / h, a temperature of 10℃, and a time of 6 h. The resulting eluent contained Li... + Concentration of 420 mg / L, Na + Concentration of 170 mg / L, K +Concentration of 35 mg / L, Mg 2+ Concentration of 74 mg / L, Ca 2+ The concentration is 5 mg / L.
[0165] (3) The desorption solution was sent into the desalination chamber of the selective electrodialysis system, and pure water was sent into the concentrate chamber as the starting solution for the concentrate. The system was run for 5 hours at a temperature of 17°C and a current density of 400 A / m. 2 .
[0166] In selective electrodialysis, a monovalent ion-poor solution is obtained from the desalination chamber, and a monovalent ion-rich solution is obtained from the concentrate chamber.
[0167] In the monovalent ion enrichment solution, the TDS was 10050 mg / L, and Li + Concentration of 885 mg / L, Na + Concentration of 360 mg / L, K + Concentration of 74 mg / L, Mg 2+ The concentration is 6 mg / L.
[0168] The lithium ion concentration in the lean monovalent ionic liquid is 43 mg / L, and the magnesium-lithium mass ratio is 1.7, which satisfies the requirement that the lithium ion concentration in the lean monovalent ionic liquid is 0.5 times higher than the lithium ion concentration in the lithium-containing oilfield produced water after ultrafiltration, and the magnesium-lithium mass ratio in the lean monovalent ionic liquid does not exceed 50. The lean monovalent ionic liquid and the lithium-containing oilfield produced water after ultrafiltration are mixed together to carry out Li adsorption in step (2).
[0169] (4) The monovalent ion enrichment solution was pumped into the forward osmosis unit (the membrane was purchased from Shanghai Tongqin Environmental Protection Technology Co., Ltd., model HTICATAES). The lithium-containing oilfield produced water after ultrafiltration was used as the draw solution for forward osmosis. The forward osmosis temperature was 23℃ and the time was 5.5h. Water molecules from the monovalent ion enrichment solution continuously permeated into the other side of the membrane. After forward osmosis, the monovalent ion enrichment solution yielded forward osmosis concentrate, the volume of which was 0.4 times that of the monovalent ion enrichment solution. The draw solution from forward osmosis was then used to obtain dilute draw solution from forward osmosis.
[0170] In the forward osmosis desalted extract, the lithium ion concentration is 61 mg / L and the magnesium-lithium mass ratio is 25, which satisfies the requirement that the lithium ion concentration in the forward osmosis desalted extract is 0.5 times higher than the lithium ion concentration in the ultrafiltration lithium-containing oilfield produced water, and that the magnesium-lithium mass ratio in the forward osmosis desalted extract does not exceed 40. The forward osmosis desalted extract and the ultrafiltration lithium-containing oilfield produced water are mixed together to carry out Li adsorption in step (2).
[0171] Li is permeating the concentrated water. + Concentration of 2040 mg / L, Na + Concentration of 830 mg / L, K +Concentration of 170 mg / L, Mg 2+ The concentration is 14 mg / L.
[0172] (5) In the bipolar membrane electrodialysis system, the forward osmosis concentrate is used as the feed water to the desalination chamber, the operating voltage is 2V, and the current density is 600A / m 2 Bipolar membrane electrodialysis was performed for 4.5 hours.
[0173] A dilute brine solution (with a lithium ion concentration of 0.21 g / L) is obtained from the desalination chamber and mixed with a monovalent ion enrichment solution for forward osmosis.
[0174] An acidic solution containing hydrogen chloride, with a hydrogen ion concentration of 0.81 mol / L, was obtained from the acid chamber and diluted for use as a desorbent for lithium adsorbent materials.
[0175] An alkaline solution containing LiOH was obtained from the alkali chamber, with a lithium ion concentration of 0.8 mol / L.
[0176] (6) Evaporate and crystallize the alkaline solution containing LiOH at 90°C to obtain a mixture of lithium hydroxide and mother liquor. After centrifuging and filtering the mixture, lithium hydroxide and mother liquor are obtained respectively.
[0177] The evaporated mother liquor is used as the draw solution for forward osmosis.
[0178] Lithium hydroxide was dissolved in water (resulting in a lithium hydroxide concentration of 95 g / L). The solution was then contacted with carbon dioxide gas in a gas-liquid reactor at 25°C until the liquid phase pH reached 11.8. The precipitate was washed, filtered, and dried to obtain lithium carbonate with a purity of 99.7% and a lithium extraction rate of 79%.
[0179] Example 3 (1) Ultrafiltration was performed on the produced water 3 from the lithium-containing oilfield. The ultrafiltration membrane (purchased from Jia Rong Technology Co., Ltd., model VFU-030 tubular ultrafiltration membrane) had a molecular weight cutoff of 30000 Da, the ultrafiltration temperature was 12℃, and the pressure was 0.19MPa.
[0180] (2) The ultrafiltration permeate (containing Li) + The lithium adsorbent material (concentration of 35.3 mg / L) and the lithium adsorbent material prepared in Preparation Example 13 were contacted in an adsorption column, and ultrafiltration permeate was pumped into the adsorption column at a rate of 3 BV / h, and adsorption was carried out at 20°C for 7 h.
[0181] After adsorption is complete, the lithium-poor ultrafiltrate is treated centrally as wastewater.
[0182] Lithium adsorbent material was desorbed using pure water as the desorbent at a flow rate of 3 BV / h, a temperature of 17℃, and a time of 7 h. The resulting eluent contained Li...+ Concentration of 545 mg / L, Na + Concentration of 155 mg / L, K + Concentration of 37 mg / L, Mg 2+ Concentration of 76 mg / L, Ca 2+ The concentration is 5 mg / L.
[0183] (3) The desorption solution was sent into the desalination chamber of the selective electrodialysis system, and pure water was sent into the concentration chamber as the starting solution for the concentration solution. The system was run for 4 hours at a temperature of 18°C and a current density of 450 A / m. 2 .
[0184] In selective electrodialysis, a monovalent ion-poor solution is obtained from the desalination chamber, and a monovalent ion-rich solution is obtained from the concentrate chamber.
[0185] In the monovalent ion enrichment solution, the TDS was 11850 mg / L, and Li + Concentration of 1205 mg / L, Na + Concentration of 350 mg / L, K + Concentration of 82 mg / L, Mg 2+ The concentration is 6 mg / L.
[0186] The lithium ion concentration in the lean monovalent ionic liquid is 48 mg / L, and the magnesium-lithium mass ratio is 1.58. This satisfies the requirement that the lithium ion concentration in the lean monovalent ionic liquid is 0.5 times higher than the lithium ion concentration in the ultrafiltration lithium-containing oilfield produced water, and that the magnesium-lithium mass ratio in the lean monovalent ionic liquid does not exceed 50. The lean monovalent ionic liquid and the ultrafiltration lithium-containing oilfield produced water are mixed together to carry out Li adsorption in step (2).
[0187] (4) The monovalent ion enrichment solution was pumped into the forward osmosis unit (the membrane was purchased from Shanghai Tongqin Environmental Protection Technology Co., Ltd., model HTICATAES). The lithium-containing oilfield produced water after ultrafiltration was used as the draw solution for forward osmosis. The forward osmosis temperature was 23℃ and the time was 6.5h. Water molecules from the monovalent ion enrichment solution continuously permeated into the other side of the membrane. After forward osmosis, the monovalent ion enrichment solution yielded forward osmosis concentrate, the volume of which was 0.5 times that of the monovalent ion enrichment solution. The draw solution from forward osmosis was then used to obtain dilute draw solution from forward osmosis.
[0188] In the forward osmosis desalted extract, the lithium ion concentration is 49 mg / L and the magnesium-lithium mass ratio is 18, which satisfies the requirement that the lithium ion concentration in the forward osmosis desalted extract is 0.5 times higher than the lithium ion concentration in the lithium-containing oilfield produced water after ultrafiltration, and the magnesium-lithium mass ratio in the forward osmosis desalted extract does not exceed 40. The forward osmosis desalted extract and the lithium-containing oilfield produced water after ultrafiltration are mixed together to carry out Li adsorption in step (2).
[0189] Li is permeating the concentrated water.+ Concentration of 2575 mg / L, Na + Concentration of 730 mg / L, K + Concentration of 176 mg / L, Mg 2+ The concentration is 13 mg / L.
[0190] (5) In the bipolar membrane electrodialysis system, the forward osmosis concentrate is used as the feed water to the desalination chamber, the operating voltage is 2V, and the current density is 600A / m 2 Bipolar membrane electrodialysis was performed for 4 hours.
[0191] A dilute brine solution (with a lithium ion concentration of 0.23 g / L) is obtained from the desalination chamber and mixed with a monovalent ion enrichment solution for forward osmosis.
[0192] An acidic solution containing hydrogen chloride, with a hydrogen ion concentration of 1.04 mol / L, was obtained from the acid chamber and diluted for use as a desorbent for lithium adsorbent materials.
[0193] An alkaline solution containing LiOH was obtained from the alkali chamber, in which the lithium ion concentration was 1.02 mol / L.
[0194] (6) Evaporate and crystallize the alkaline solution containing LiOH at 80°C to obtain a mixture of lithium hydroxide and mother liquor. After centrifuging and filtering the mixture, lithium hydroxide and mother liquor are obtained respectively.
[0195] The evaporated mother liquor is used as the draw solution for forward osmosis.
[0196] Lithium hydroxide was dissolved in water (resulting in a lithium hydroxide concentration of 93 g / L). The solution was then contacted with carbon dioxide gas in a gas-liquid reactor at 25°C until the liquid phase pH reached 11.9. The precipitate was washed, filtered, and dried to obtain lithium carbonate with a purity of 99.5% and a lithium extraction rate of 80%.
[0197] Example 4 The oilfield produced water 1 was treated according to the method of Example 1, except that the lithium adsorbent was replaced with the lithium adsorbent prepared in Preparation Example 1. 0.5 mol / L hydrochloric acid was used as the desorbent to desorb the lithium adsorbent, and the other steps were exactly the same as in Example 1, yielding a lithium carbonate product with a purity of 99.7% and a lithium extraction rate of 82.5%.
[0198] Example 5 The oilfield produced water 1 was treated according to the method of Example 1, except that the lithium adsorbent was replaced with the lithium adsorbent prepared in Preparation Example 3. 0.4 mol / L hydrochloric acid was used as the desorbent to desorb the lithium adsorbent, and the other steps were exactly the same as in Example 1, yielding lithium carbonate product with a purity of 99.2% and a lithium extraction rate of 79.6%.
[0199] Example 6 The oilfield produced water 1 was treated according to the method of Example 1, except that the lithium adsorbent was replaced with the lithium adsorbent prepared in Preparation Example 5. 0.3 mol / L hydrochloric acid solution was used as the desorbent to desorb the lithium adsorbent. All other steps were exactly the same as in Example 1, yielding a lithium carbonate product with a purity of 99.4% and a lithium extraction rate of 81.4%.
[0200] Example 7 The oilfield produced water 1 was treated according to the method of Example 1, except that the lithium adsorbent was replaced with the lithium adsorbent prepared in Preparation Example 6. The lithium adsorbent was desorbed using a 0.6 mol / L hydrochloric acid solution as a desorbent, and the other steps were exactly the same as in Example 1, yielding a lithium carbonate product with a purity of 98.7% and a lithium extraction rate of 78.8%.
[0201] Example 8 The oilfield produced water 1 was treated according to the method of Example 1, except that the lithium adsorbent was replaced with the lithium adsorbent prepared in Preparation Example 7. The lithium adsorbent was desorbed using a 0.35 mol / L hydrochloric acid solution as a desorbent, and all other steps were exactly the same as in Example 1, yielding a lithium carbonate product with a purity of 98.1% and a lithium extraction rate of 78.1%.
[0202] Comparative Example 1 The oilfield produced water 1 was treated according to the method of Example 1. The difference was that after the desorption solution was subjected to selective electrodialysis, the monovalent ion enrichment solution was directly introduced into the bipolar membrane electrodialysis system. The other steps were exactly the same as in Example 1, and lithium carbonate product with a purity of 91% and a lithium extraction rate of 68% was obtained.
[0203] The results above show that the method provided by this invention can extract lithium from materials with significantly low lithium concentration with high yield and purity. It is particularly suitable for low-grade oilfield produced water, and the process is simple, with low operating costs, short lithium extraction cycle, strong continuity, and no additional pollution.
[0204] Examples 1 and 4-8 show that when using the lithium extraction method provided by the present invention, and in conjunction with the lithium adsorbent material with a higher adsorption capacity preferred by the present invention, the lithium adsorbent material required by the present invention is less when the lithium ion content in the oilfield produced water is certain, which also saves production costs to a certain extent.
[0205] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for treating produced water from lithium-containing oilfields, characterized in that, The method includes: (1) Ultrafiltration of produced water from lithium-containing oilfields; (2) Using lithium adsorption material, Li adsorption is performed on ultrafiltration produced water containing lithium from the oilfield to obtain produced water with Li adsorption; the lithium adsorption material is desorbed to obtain desorbed liquid; the lithium adsorption material includes a framework and lithium ion sieve material dispersed in the framework, the lithium ion sieve material is connected to the framework by a coupling agent, the framework is provided by a cross-linked or uncross-linked polyhydroxy polymer; the lithium ion sieve material is a lithium ion sieve material modified with polyphenols; (3) The desorption solution is enriched with monovalent ions to obtain a monovalent ion-poor solution and a monovalent ion-enriched solution; (4) The monovalent ion enrichment solution is subjected to forward osmosis to obtain forward osmosis concentrate; (5) The forward osmosis concentrate is subjected to bipolar membrane electrodialysis to obtain an alkaline solution containing LiOH.
2. The method according to claim 1, wherein, In step (1), the operating conditions for ultrafiltration include: a temperature of 5-30℃ and a pressure of 0.1-0.4MPa.
3. The method according to claim 1, wherein, In step (2), the operating conditions for Li adsorption include: an adsorption flow rate of 1.8-3 BV / h, a temperature of 8-30℃, and a time of 5.5-8h. And / or, in step (2), the desorption operating conditions include: the desorption flow rate of the desorbent is 1.8-3 BV / h, the temperature is 8-30℃, and the time is 5.5-8h.
4. The method according to claim 1, wherein, The method of enriching monovalent ions is selected from selective electrodialysis and / or nanofiltration.
5. The method according to claim 4, wherein, The method for enriching monovalent ions is selective electrodialysis.
6. The method according to claim 5, wherein, The operating conditions for the selective electrodialysis include: a current density of 400-500 A / m³. 2 Temperature 10-30℃, time 4-6 hours.
7. The method according to claim 1, wherein, When the lithium ion concentration in the lean monovalent ionic liquid is higher than 0.5 times the lithium ion concentration in the ultrafiltration lithium-containing oilfield produced water, and the magnesium-lithium mass ratio in the lean monovalent ionic liquid does not exceed 50, the method further includes: mixing the lean monovalent ionic liquid and the ultrafiltration lithium-containing oilfield produced water together to carry out Li adsorption in step (2).
8. The method according to claim 1, wherein, The operating conditions for the forward osmosis include: temperature 10-30℃ and time 3-12h.
9. The method according to claim 1, wherein, The operation mode of the bipolar membrane electrodialysis includes: using forward osmosis concentrate as feed water to the desalination chamber, operating voltage of 2-3V, and current density of 600-900A / m³. 2 The time is 4-5 hours.
10. The method according to claim 1, wherein, After step (5), the method further includes: extracting LiOH from the alkaline solution containing LiOH, and contacting LiOH with carbon dioxide to react and obtain lithium carbonate.
11. The method according to claim 1, wherein, The quality of produced water from lithium-containing oil fields includes: Li + The concentration is 25-80 mg / L, and the concentration of alkaline earth metal ions is 1000-15000 mg / L.
12. The method according to claim 11, wherein, The quality of produced water from lithium-containing oil fields includes: Li + Concentration of 35-70 mg / L, Na + Concentration of 3100-3500 mg / L, K + Concentration of 290-320 mg / L, Mg 2+ Concentration of 1100-1350 mg / L, Ca 2+ Concentration of 35-55 mg / L, Cl - Concentration of 8700-9000 mg / L, SO4 2- The concentration is 1700-2100 mg / L, the pH is 7.1-8.5, the total organic matter is 500-1600 mg / L, and the total dissolved solids are 35000-38000 mg / L.
13. The method according to claim 1, wherein, The average particle size of the lithium adsorbent material is 1-5 mm.
14. The method according to claim 1, wherein, The average particle size of the lithium adsorbent material is 2-4 mm.
15. The method according to claim 1, wherein, The mass content of lithium ion sieve material is 10-80 wt% relative to the mass of lithium adsorbent material.
16. The method according to claim 15, wherein, The mass content of lithium ion sieve material is 68-77 wt% relative to the mass of lithium adsorbent material.
17. The method according to claim 1, wherein, The specific surface area of the lithium adsorbent material is 10-500 m². 2 / g.
18. The method according to claim 17, wherein, The specific surface area of the lithium adsorbent material is 10-45 m². 2 / g.
19. The method according to claim 1, wherein, The lithium adsorbent material has an average pore size of 0.1-10 μm.
20. The method according to claim 19, wherein, The lithium adsorbent material has an average pore size of 2-5 μm.
21. The method according to claim 1, wherein, The lithium adsorbent material has a pore volume of 10-100 cm³. 3 / g.
22. The method according to claim 21, wherein, The lithium adsorbent material has a pore volume of 50-85 cm³. 3 / g.
23. The method according to claim 1, wherein, At 25°C, the lithium adsorbent material has a water absorption rate of 0.1-0.18 g / g for pure water and a volume swelling rate of 2-10%.
24. The method according to claim 1, wherein, The average particle size of lithium-ion sieve materials is 10-500 μm.
25. The method according to claim 1, wherein, The polyhydroxy polymer is selected from at least one of polyvinyl alcohol, chitosan, polyethylene glycol, and carboxymethyl cellulose.
26. The method of claim 25, wherein, The polyhydroxy polymer is polyvinyl alcohol.
27. The method according to claim 1, wherein, The coupling agent is selected from silane coupling agents.
28. The method according to claim 27, wherein, The silane coupling agent is selected from at least one of thiol-containing silane coupling agents and epoxy-containing silane coupling agents.
29. The method according to claim 28, wherein, The silane coupling agent is an epoxy-containing silane coupling agent.
30. The method according to claim 29, wherein, The epoxy-containing silane coupling agent is selected from at least one of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane.
31. The method according to claim 1, wherein, The method for polyphenol modification includes: mixing lithium ion sieve material with polyphenols to modify the lithium ion sieve material.
32. The method according to claim 31, wherein, The mixing takes place in a solution environment.
33. The method according to claim 31, wherein, The mass ratio of lithium-ion sieve material to polyphenol is 1:(0.08-0.3).
34. The method according to claim 31, wherein, The mixing time is 1-3 hours.
35. The method according to claim 31, wherein, The polyphenols are selected from at least one of tannic acid, tea polyphenols, dopamine, sennaol, epicatechin, luteolin, calciferol, myricetin and genistein.
36. The method according to claim 35, wherein, The polyphenols are selected from at least one of tannic acid, tea polyphenols and dopamine.
Citation Information
Patent Citations
Method for preparing battery-grade lithium carbonate
CN109987618A
Process for extracting lithium from salt lake brine by adsorptive method
CN1511964A
Process for preparing lithium carbonate by extracting lithium from oilfield underground brine
CN113511663A